The emerging role and therapeutic implications of bacterial and parasitic deubiquitinating enzymes - Wehrmann, Markus; Vilchez, David (Frontiers in Immunology, 2023)
Deubiquitinating enzymes (DUBs) are emerging as key factors for the infection of human cells by pathogens such as bacteria and parasites. In this review, we discuss the most recent studies on the role of deubiquitinase activity in exploiting and manipulating ubiquitin (Ub)-dependent host processes during infection. The studies discussed here highlight the importance of DUB host-pathogen research and underscore the therapeutic potential of inhibiting pathogen-specific DUB activity to prevent infectious diseases.